ANALISIS PENERAPAN SISTEM INFORMASI PEMERINTAH DAERAH (SIPD) PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) KOTA MEDAN - Nasution, Muhammad Irfan; M.Si, Nurwani (Department of Accounting, Faculty of Economics & Business, 2021)
SIPD or local government Information System is an information system used in medan city government as a regional development planning system, regional financial system, as well as other local government systems, including the system of coaching and supervision of local government. However, the application of SIPD, especially in Medan, has not been carried out properly because of the quality of the system that is still lacking, in addition to the lack of efficiency in terms of time or the short time needed to conduct technical guidance causes many SKPD not yet accustomed to using SIPD. The purpose of this research is to find out how sipd implementation in Medan.. Research method used is descriptive research using qualitative approach. Based on the results of the research that has been carried out, it shows that the Medan City BPKAD has used the Regional Government Information System (SIPD) application to carry out the policies needed to carry out various activities which are programs from the Medan city government. and Based on the information obtained, the Regional Government Information System (SIPD) functions to contain the regional development planning system and regional financial system, as well as other regional government systems, including the regional government guidance and supervision system.